Estimation of serum ascorbic acid (vitamin C) in various morphological types and clinical stages of age related (senile cataract) - Angirekula, Saseekala; Atti, Lalitsiri; Atti, Srihari (International Journal of Research in Medical Sciences, 2018)
Background: The aim was to estimate the serum ascorbic acid (vitamin C) in the various morphological types and clinical stages of age related (senile) cataract, a common cause of curable blindness globally, especially in India. Methods: This was a study of estimation of serum ascorbic acid (vitamin C) in 100 cases of senile (age related) cataract with 60 cases of senile cortical type (30 cases of immature and 30 cases of mature) and 40 cases of senile nuclear type (20 cases of grades I and II and 20 cases of grades III and IV) in the age group of 45 to 70 years. Results: Vitamin C mean plasma level was significantly decreased in senile cataract (0.54±0.23mg/dl or 30.68±13.07umol) and in its morphological types of cortical and Nuclear, especially in the later stages or grades of maturity when compared with the earlier stages or grades of immaturity i.e. The mean level of Serum Ascorbic acid was 0.55±0.23 mg/dl ((31.25±13.07umol) in Senile Cortical cataract with 0.58±0.24 mg/dl (32.96±13.64umol) in its Immature stage and 0.52±0.20mg/dl (29.55±11.36umol) in its mature stage and the mean level in Senile Nuclear cataract was 0.54±0.23mg/dl (30.68±13.7umol) with 0.56±0.29mg/dl (31.82±16.48umol) in its Grades I and II and 0.52±0.22mg/dl (29.55±12.5umol) in its Grades III and IV. Conclusions: So, our study showed significantly decreased levels of serum vitamin C in all the morphological types and clinical stages of senile cataract especially in the later stages or grades of maturity compared to the earlier clinical stages or grades of immaturity.